Study on the Security Access Technology of Business Platform Communication Network - 陈捷 (Dianxin kexue)
Combined with the features of telecom operator communications network, the security access technology from business platform to signaling network was discussed, and the key technology about business platform accessing security gateway was elaborated. The construction ideas about signaling security gateway was proposed.